Analysis of Islamic Religious Education (IRE) Learning in Strengthening Religious Character in Elementary Schools of Belitang Madang Raya Sub-District, East OKU Regency - Istiana, Istiana; Yuberti, Yuberti; Akmansyah, Muhammad (Universitas Sang Bumi Ruwa Jurai, 2025)
The strengthening of students’ religious character is a key objective of Islamic Religious Education (IRE) in elementary schools. This study aimed to analyze the implementation of IRE learning in fostering religious values among elementary students in the Belitang Madang Raya Sub-District, East OKU Regency. Employing a qualitative descriptive approach with a case study design, data were collected through classroom observations, in-depth interviews with teachers, principals, and students, and documentation analysis. The findings revealed that religious character values, such as honesty, responsibility, social awareness, and discipline, were effectively instilled through integrated learning strategies, religious routines, and teacher role modeling. Supporting factors included a religious school culture, cooperation with parents and communities, and the presence of Islamic-based programs. However, several obstacles were identified, such as limited awareness among some students and educators and the dominance of cognitive-oriented teaching methods. Overall, the study highlights the importance of holistic strategies and collaborative efforts in fostering religious character, offering insights for broader implementation in similar sociocultural contexts.